The role of parental support and pressure on athletic success: an exploratory study on youth athletes' development - Wasihun Abate Sentie; Belayneh Chekle; Tesfay Asgedom (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Parental involvement plays a pivotal role in shaping the athletic development and psychological well-being of young athletes. While support can enhance motivation and performance, excessive pressure may lead to anxiety and emotional distress. Understanding this dynamic is essential in promoting healthy youth sports experiences.